KONVERGENSI AGAMA DAN SAINS DALAM MELACAK BASIS ONTOLOGI SEMESTA: Tinjauan Hermeneutika Hadis Penciptaan - Mustofa Umar (Jurnal Theologia, 2016)
Abstract: The main purpose of this article (research) is to provide the unity of coherent conceptual frameworks between religion and science on the discourse about the origins of the universe. Contemporary cosmological theories reveal the continuing encounter between physics and theology (religion). The concepts of modern physics show surprising parallels to the ideas expressed in the religious philosophies that the basic features of their worldview are the same. Mystical traditions are present in all religions and they also can be found in the theory of modern physics on the holistic conception of reality. It obviously indicates a new “paradigm”— a new vision of reality. By the “antinomic” principles of light, both religion and science, ontologically, can trace the beginning of the universe, and also unveil the deepest secrets of the laws of physics. Light as the basic ontology of reality in the hadith texts has been used by muslem theosophists (sufi) to formulate their theories of the universe creation, especially, in the sufism of Ibn Arabi. His cosmological concepts are essentially similar to the scientific conceptions of cosmology and completely in accordance with the laws of physics in the very heart of the cosmos itself. At the moment, the integration of religion and science has arrived at the same holistic conception of reality. As the pillar of civilization, both are expected to go hand in hand and form a powerful force for social change in the new conceptual frameworks for ways of life, thought, and consciousness. Abstrak: Tujuan utama dari artikel (riset) ini adalah untuk membuktikan terdapatnya kesatuan kerangka konseptual yang koheren antara agama dan sains tentang persoalan muasal alam semesta. Teori-teori kosmologi modern menunjukkan adanya titik temu yang berkelanjutan antara sains dan teologi (agama). Konsep-konsep fisika modern memperlihatkan kesejajaran yang menakjubkan terhadap ide-ide yang diungkapkan dalam filsafat agama, yaitu ciri-ciri dasar pandangan mereka yang sama. Tradisi-tradisi mistik yang terdapat dalam agama, juga dapat dijumpai dalam teori fisika modern tentang konsep realitas yang holistik. Ini dapat disebut sebagai paradigm baru-visi baru terhadap realitas. Melalui prinsip “antinomi” cahaya, secara ontologis, agama dan sains keduanya dapat melacak permulaan semesta, juga dapat membuka selubung terdalam dari rahasia hukum alam (sunnatullāh). Cahaya sebagai basis ontology realitas yang terdapat dalam teks-teks hadis, telah digunakan oleh para sufi untuk menformulasikan teori-teori mereka tentang penciptaan semesta, khususnya Ibn Arabi. Secara esensial, konsep kosmologi Ibn Arabi memiliki kemiripan dengan konsepsi dalam sains dan secara sempurna sesuai dengan hukum alam pada aspek yang paling dalam dari kosmos itu sendiri. Saat ini, intregrasi agama dan sains sudah sampai pada kesamaan konsepsi tentang realitas secara holistik. Sebagai pular peradaban, keduanya diharapkan dapat berjalan beriringan dan membentuk sebuah kekuatan penuh bagi perubahan sosial dalam bingkai keonseptual baru terhadap pandangan hidup, pemikiran dan kesadaran.